Environmental Responsibilities and Firms Financial Performance: A Systematic Review and Bibliometric Analysis - Mohit Verma; Mukhtaruddin Mukhtaruddin (Universitas Pasundan, 2023)
The aim of this study is to present a systematic review and bibliometric analysis of 512 studies on environmental responsibilities and firm financial performance literature. The study aims to track the research trend and identify the reasons behind heterogeneity in the studied association. The Scopus database was comprehensively searched to collect bibliographic material, giving an overview of contributing and influential research areas, key authors, journals, and countries. Network visualization is used to identify clusters. Content analysis of the literature revealed the essential topics of the investigation. The systematic review revealed that geographical constraints, regulatory constraints, and lack of standardizability are significant reasons for heterogeneity. We identify three major researched areas: a) economic and financial impact, b) innovation, environment management system, and standards, and c) supply chain management development. Discussion on the significant clusters concludes that studies showing positive economic benefits dominate the literature. Overall, the results of different scientific production do not indicate consensus in one direction, but mixed results help to build a new perspective and expand the research horizon. Using a systematic process, this study recognizes the value-creation potential of proactive environmental management practices.